Histomorphogenesis of Sweat Gland in Prenatal Goat (Capra hircus) - Kumar, Prabhakar (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted 36 goat embryo/ foetus to record the sequential histological changes that take places during the development of sweat gland in the skin of prenatal goat. The material was divided into three groups containing 12 foetuses in each group. The primordia of the sweat glands first appeared as bud like structure in face region at 84 days gestation, then in chin region at 87 days and from 94 days gestation in all body regions. Subsequently, the primordial elongated to become cylindrical cord like structure and lumen formation started in chin and face regions at 94 days and in all body regions from 106 days gestation. The luminal part of the glands had outer flattened cells and inner cuboidal cells layer with rounded centrally placed vesicular nuclei and eosinophilic cytoplasm. Coiling of luminal part of glands began at 102 days gestation in chin region and from 145 days gestation in all body regions. Myoepithelial cells were interposed between basement membrane and lining epithelial cells from 102 days gestation.